(untitled) (IIUC Studies, 2016)
The main concern of this paper is to explore the status of Chittagonian variety- a language spoken by the people of Chittagong in Bangladesh-with a view to considering whether it is a dialect of Bangla or a language or a semi-language. Though it is closely related to Bangla, its distinctive features like a different sound system, mutual unintelligibility with Bangla, etc. give it a separate entity and encourage the researcher of this paper to rethink about the existing idea of its being a dialect of Bangla and to try to present some supportive argumants in favor of its separate entity as a language. In the article the researcher has provided an introduction to the Chittagonian variety; language and dialect; previous literature, and used methodology consisting of random sampling based on the collection of newspaper articles, books, and internet sources, and the like. And some findings from that research and recommendations have been discussed. IIUC Studies Vol.12 December 2015: 41-62